Is there any room for PD-1 inhibitors in combination with platinum-based chemotherapy as frontline treatment of extensive-stage small cell lung cancer? A systematic review and meta-analysis with indirect comparisons among subgroups and landmark survival analyses. (July 2021) - Gristina, Valerio; Galvano, Antonio; Castellana, Luisa; Insalaco, Lavinia; Cusenza, Stefania; Graceffa, Giuseppa; Iacono, Federica; Barraco, Nadia; Castiglia, Marta; Perez, Alessandro; Rizzo, Sergio; Russo, Antonio; et al.
Background: The addition of PD-L1 inhibitors to platinum-based chemotherapy (CT) has newly received United States Food and Drug Administration (FDA) approval in extensive stage-small cell lung cancer (ES-SCLC). PD-1 agents similarly improved survival rates, even if not yet supported by international regulatory agencies. The current work aims to assess different efficacy and safety profiles among chemoimmunotherapy plus immuno-oncology (CT+IO) approaches according to different immune checkpoint inhibitor (ICI) subtypes. Material & Methods: We included in our meta-analysis six first-line randomised controlled trials (RCTs) comparing the association of single-agent ICI with CT versus CT alone in ES-SCLC. Pooled hazard ratios (HRs) and risk ratios (RRs) for progression-free survival (PFS), overall survival (OS), objective response rates (ORR), 12-month duration of response rate (DORR), disease control rate (DCR), treatment-related adverse events (TRAEs) and discontinuation rates (DRs) were obtained. Moreover, we performed indirect comparisons according to ICI subtypes, also among subgroups and landmark survival analyses. Results: Although no ORR benefit was observed, our results showed how CT+IO significantly improved DORR, resulting in improved PFS and OS with no differences in TRAEs; however, CT+IO led to a significant increase in DR. Interestingly, an Eastern Cooperative Oncology Group performance status (ECOG PS) of 1, the use of cisplatin, and the absence of brain metastases seem to be associated with a survival gain using CT+IO in ES-SCLC. Indirect comparisons suggested a slight advantage in favour of programmed cell death-1 (PD-1) and programmed death ligand 1 (PD-L1) over anti-CTLA-4 agents in terms of efficacy with no additional safety concerns. No further differences were observed between PD-1 and PD-L1 inhibitors among subgroups and landmark survival analyses with benefit trends towards anti-PD-1 in terms of DORR and DR. Conclusion: While confirming a survival advantage of CT+IO in selected patients, these results suggested the association of PD-1 inhibitors with CT as a viable option for novel therapeutic approaches in the frontline management of ES-SCLC. Further trials evaluating anti-CTLA-4 agents should be carefully studied in biomarker-selected patients.